Financial Knowledge and Financial Attitude Towards The Personal Financial Management Behavior Of MSME Entreprenuer - Nuriani; Arfandi Dinsar; Hamida Hasan (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2022)
Personal Financial behavior is a person's ability to manage, namely planning, budgeting, assessing, executing, controlling, seeking, and storing financial funds daily. This study aimed to determine the extent to which financial knowledge and attitudes influence personal financial management behavior. This type of research is Descriptive Quantitative. The data collection technique uses questionnaires that are distributed directly to 63 MSME Entrepreneurs Through Google Forms using a purposive sampling method. The sample in this study is an MSME entrepreneur in Makassar City. Methods of data analysis in this study using the validity test, reliability test, partial test, concurrent test, and test the coefficient of determination using SPSS V.23 software. Based on the results of research data analysis, it can be concluded that financial knowledge and attitude positively affect personal financial management behavior. The limitation, is because this research only focuses on MSME entrepreneurs and one city, the results may not be generalizable. In addition, the relatively small sample size may be another limitation of this study.